(untitled) (Journal of Laboratory Animal Science, 2025)
Outbred rats are laboratory animals widely used in preclinical research and investigation of clinical pathology parameters is an important part of the preclinical evaluation of drug safety. The objective of the present study was to determine the influence of strain and age on selected haematological and biochemical analytes in Sprague Dawley (Crl:CD[SD]) and Wistar (Crl:WI[Han]) rats. Selected analytes were studied in 390 rats per strain with an equal representation of both sexes at 6-8 weeks, 10-14 weeks and 6-10 months of age. The data were statistically compared to assess the changes in relation to age and strain. The distribution of results by strain showed that SD rats of both sexes had significantly higher values of MCHC, PLT, WBC, LYMPH and AST, ALT concentration, while male Wistar rats had significantly higher values of RBC, E% and female Wistar rats had N% and UREA concentration. The distribution of the results according to age showed that the increase in the age of the rats significantly reduced the MCV, MCH, PLT, L%, and the concentration of AST, ALP. The concentration of GLU, TP, CREA and percentage of neutrophil and eosinophil significantly increased with the increasing age of rats. In conclusion, this research demonstrated that age and strain significantly influence most of the hematological and biochemical parameters of outbred rats.